Premios Novartis en el Museo Nacional de Bellas Artes. - Glusberg, Jorge; Villalba, Luis (Buenos Aires : MNBA - Museo Nacional de Bellas Artes Buenos Aires, 1997)
Aisenberg, Diana ; Alvaro, Jorge ; Angriman, Christian ; Aslan, Nora ; Astica, Juan ; Bedel, Jacques ; Bertani, Ernesto ; Bissolino, Carlos ; Boullosa, Marcelo ; Brewda, Silvia ; Briuolo, Marta ; Carletti, Alicia ; Castillo, Victor ; Cetner, Eduardo ; Cohen, Sibyl ; Collaud, Luchi ; Compagnucci, Andrés Gaston ; Doffo, Juan ; Dowek, Diana ; Elissamburu, Oscar ; Figueroa, Marcos ; Finochietti, María ; Frangella, Roberto Roque ; Gallardo, Ana ; Garcia, Daniel ; Garnica, Jorge ; Ghetti, Cristina ; Girolamo, Martin Di ; Golubinsky, Liliana ; Gravinese, Diego ; Herrero, Alicia ; Houghton, Marcelo ; Joao, Maria Ester ; Jozami, Daniela ; Koroluk, Maria Alejandro ; Laurencena, Hugo ; Lecuona, Juan ; Lindner, Luis ; Maddonni, Alejandra viviana ; Mangiante, Nuna ; Médici, Héctor ; Melcom, Miguel ; Mirocznyk, Gabriel ; Mitia, Alex ; Molek, Amalia Perez ; Montoya, Victor ; Monzo, Osvaldo ; Niveiro, Luis ; Noya, Ana Dolores ; Ortiz, Agustin ; Páez, Oscar ; Pederiva, Carlos ; Perez, Mario ; Perrin, Jorge Gonzalez ; Polesello, Rogelio ; Prior, Alfredo ; Ranieri, Juan ; Risso, Enrique Burone ; Rivas, Silvia ; Rojas, Laura ; Rotella, Eduardo Javier Lopez ; Rudnik, Daniela ; de Sagastizábal, Tulio ; Salvioli, Marcelo ; Sapia, Mariano ; Saravia, Susana ; Scafidi, Roberto ; Sequier, Pablo ; Socolovsky, Paula ; Soria, Chino ; Strasberg, Liana ; Suarez, Oscar ; Tenebaum, Leon ; Tomas, Marcelo di ; Torreta, Marcelo ; Torroja, Enrique ; Traverso, Fernando ; Venturini, Andrea ; Videla, Juan Andres ; Waissman, Andres ; Wells, Luis ; Young, Silvia ; Zorreguieta, Dolores ; Zuik, Martha
biografie
Spaans
boek